Biogeochemical gradients above a coal tar DNAPL - Scherr, K.; Backes, D.; Scarlett, Alan; Lantschbauer, W.; Nahold, M. (2015)
Naturally occurring distribution and attenuation processes can keep hydrocarbon emissions from dense non aqueous phase liquids (DNAPL) into the adjacent groundwater at a minimum. In a historically coal tar DNAPL-impacted site, the de facto absence of a plume sparked investigations regarding the character of natural attenuation and DNAPL resolubilization processes at the site. Steep vertical gradients of polycyclic aromatic hydrocarbons, microbial community composition, secondary water quality and redox-parameters were found to occur between the DNAPL-proximal and shallow waters. While methanogenic and mixed-electron acceptor conditions prevailed close to the DNAPL, aerobic conditions and very low dissolved contaminant concentrations were identified in three meters vertical distance from the phase. Comprehensive two-dimensional gas chromatography-mass spectrometry (GC. ×. GC-MS) proved to be an efficient tool to characterize the behavior of the present complex contaminant mixture. Medium to low bioavailability of ferric iron and manganese oxides of aquifer samples was detected via incubation with Shewanella alga and evidence for iron and manganese reduction was collected. In contrast, 16S rDNA phylogenetic analysis revealed the absence of common iron reducing bacteria.Aerobic hydrocarbon degraders were abundant in shallow horizons, while nitrate reducers were dominating in deeper aquifer regions, in addition to a low relative abundance of methanogenic archaea. Partial Least Squares - Canonical Correspondence Analysis (PLS-CCA) suggested that nitrate and oxygen concentrations had the greatest impact on aquifer community structure in on- and offsite wells, which had a similarly high biodiversity (H' and Chao1). Overall, slow hydrocarbon dissolution from the DNAPL appears to dominate natural attenuation processes. This site may serve as a model for developing legal and technical strategies for the treatment of DNAPL-impacted sites where contaminant plumes are absent or shrinking.